THREATS TO INDUSTRIAL POLICY, TRADE AND KNOWLEDGE SHARING IN A GLOBAL EMERGENCY - T. V. Bakhturazova; M. K. Mayorov; N. V. Mayorova; D. A. Edelev (Вестник университета)
The coronavirus epidemic 2019-nCoV in China has already led to a slowdown in the country’s economic growth and the fall of the yuan exchange rate on the stock exchanges. The Russian government has banned visa-free tourist trips between Russia and China and the issuance of work visas to Russia for Chinese citizens; Australia, New Zealand, Japan, Pakistan, and Italy have imposed similar bans. Great Britain, South Korea, Singapore and New Zealand have imposed quarantine for arrivals from China. Military aircrafts of Russia, India and Thailand take their citizens out of China. The US authorities have declared public health emergency and ban on the entry of all foreign citizens who have visited China over the past two weeks. This article gives forecast, how these measures of the governments will affect on global academic mobility and economic growth.